COMPLIANCE OF ENVIRONMENTAL DOCUMENTS SUBMISSION BY BADUNG’S COMMUNITY: A COMPARATIVE STUDY WITH CHON BURI THAILAND’S COMMUNITY - Cahaya, Bunga Lily; Widiatedja, I Gusti Ngurah Parikesit; Satyawati, Ni Gusti Ayu Dyah (Kertha Semaya : Journal Ilmu Hukum; Vol 12 No 8 (2024), 2024)
There has been a close relationship between the level of compliance and the success of environmental programs. The current environment program may end up damaging the lives of the surrounding community if the relevant community does not comply. Therefore, this article aims to provide understanding to the law scholars regarding the changes that occurred in Law No. 32 of 2009 concerning Environmental Protection and Management after the enactment of Law No. 6 of 2023 concerning the Establishment of Government Regulation in Lieu of Law No. 2 of 2022 concerning Job Creation, as well as the compliance of the people of Badung Regency in submitting environmental documents when compared with the people of Chon Buri, Thailand. This study employs empirical methods, namely research with a statute, fact, and comparative approaches. The results of the research show that the degree of compliance among the residents of the two regions remains poor due to some factors, including a lack of awareness of the importance of environmental health, the complicated and lengthy process of applying for environmental permits, and unclear information from the government in regards to monitor the environmental permits.